Nikah Sirri dan Pengaruhnya pada Kesejahteraan Keluarga (Studi Kasus di Desa Puspanegara, Kecamatan Citeureup) - Muhammad Wildan Arrosyid; Sutisna Sutisna; Hambari Hambari (KOLONI, 2023)
Currently in Indonesia unregistered marriages or unregistered marriages are still common among ordinary people, because they are considered to be cheaper to implement and are a way out with a quick procedure and are considered legal. The aim of this research is to find out more about the factors that support the occurrence of sirri marriages in Puspanegara village, Citereup District, Bogor Regency and their influence on family welfare and to look in depth at the views of Islamic law and positive law on sirri marriages. The method used in this research is descriptive qualitative research and the technique for determining the sample is the snowball sampling technique. The results of this research show that the factors that cause people in Puspanegara Village, Citereup District, Bogor Regency to carry out unregistered marriages are due to a lack of understanding of marriage registration regulations, economic factors, the occurrence of pregnancies outside of marriage, parental coercion, the absence of a divorce certificate and the community's views. This kind of marriage has effects such as the wife and children not being able to claim their rights, such as the difficulty of obtaining birth certificates and children's schooling, the difficulty of obtaining rights to inheritance or shared assets, it can give rise to new poverty, marriages become vulnerable and cannot be maintained and trigger the emergence of polygamy. wild. It is hoped that the government, both village officials and the local KUA, will work together with various parties to hold outreach or counseling regarding the necessity of carrying out official marriages and provide education about the consequences and risks associated with unregistered marriages in the Puspanegara Village Community, Citeureup District, Bogor Regency, as well as holding mass marriage isbats.